Comprehensive Analysis of Trypoxylus dichotomus: Inorganic Elements, Amino Acids, and Bioactive Compounds and Their Anticancer, Antioxidant, and Neuroprotective Properties - Dongyan Ye; Qianhui Li; Xuwen Liu; Jie Zhou; Shuren Yin; Suyi Zhang; Jing Wang; Kh Ahammad Uz Zaman; Helong Bai; Fanlei Meng (Molecules)
The Compendium of Materia Medica highlights the therapeutic properties of Trypoxylus dichotomus (T. dichotomus). In this study, the species and content of volatile components, inorganic elements, and amino acids were measured, and the activity of crude extracts of ethanol and water was studied. GC-MS analysis revealed 37–53 components across different life stages, excluding excessive heavy metals and containing essential trace elements. Amino acid profiling identified 15 types, rich in seven medicinal varieties. The in vitro anti-tumor testing of ethanol extracts from T. dichotomus adult males (TDA (M)) and T. dichotomus adult females (TDA (F)) was also performed. The experimental results showed that TDA (M) exhibited growth inhibition rates of 86.22% ± 1.19%, 85.42% ± 0.63%, 88.15% ± 3.27%, and 97.23% ± 0.60% against MKN-45, K-562, 239T, and 5637 tumor cells, respectively, while TDA (F) showed 81.28% ± 5.06% inhibition against K-562 cells. TDA best protected cells induced by H2O2 at the concentration of 12.5 μg/mL, achieving a cell survival rate of 81%. Overall, TDA, TDA(F), and TDA(M) have notable anti-tumor and antioxidant activity, highlighting the significance of chemical analysis for their potential bioactivity.